Legal Consequences of a Deed of Gift Made by Spouses (Case Study of Deed of Gift No. 937 Dated December 27, 2016) - Kholifah, Kholifah (Dinasti Research, 2025)
The land is the settlement place for most of the community, besides being a source of livelihood for those who earn a living through farming and plantations. Ultimately, the land also serves as the final resting place for someone who has passed away. The population of Indonesia continues to grow, but the land area remains unchanged. The available land area eventually becomes disproportionate to the increasing population. How people meet their needs for land includes buying and selling, exchanging, gifting, or through bequests. This journal will discuss the legal consequences of a grant deed made by a married couple still in the bond of marriage from the perspective of the law. The law has regulated the procedures on how grants are to be made and the legal subjects allowed to execute the grants